Comparison of Historical Materials for High School and Vocational School in 2013 Curriculum and the Emergency Curriculum - Asyif Awaludin Romadhoni; Aman Aman; Raden Roro Anisa Khaura (AL-ISHLAH: Jurnal Pendidikan, 2023)
As a result of the covid epidemic, high schools shifted from using the 2013 curriculum to using the emergency curriculum. The purpose of this research was to examine and contrast the emergency curriculum implemented during the pandemic with the high school and vocational school history content from 2013. This research was qualitative in nature, employing a case study approach. The purpose of this study is to investigate the Emergency Curriculum's content standards for high school Indonesian history courses, namely its core competencies and fundamental competencies. There was no discernible shift in the outcomes when comparing the Covid-19 Pandemic Emergency Curriculum to the Core Competencies of Indonesian History in the 2013 Curriculum. This demonstrates that the 2013 Curriculum's key skills served as a foundation for the development of the Covid-19 Pandemic Emergency Curriculum's core competencies. In this situation, there is no significant variation in the kind of competence that students at each grade level in senior High School are expected to acquire. There were ten fewer KD heads in class XI. This occurred because the ideal conditions for learning at a distance were not met. Five KD in competency success indicators tailored to distant learning development is sufficient for pupils to pass class XII of the Covid-19 Pandemic Emergency Curriculum.